2000
DOI: 10.1021/ja002588f
|View full text |Cite
|
Sign up to set email alerts
|

Dodecahedryl Anion Formation and an Experimental Determination of the Acidity and C−H Bond Dissociation Energy of Dodecahedrane

Abstract: Dodecahedryl anion (1a) was generated in a Fourier transform mass spectrometer by deprotonation of dodecahedrane (1). Examination of the acid and base behavior of 1 and 1a, respectively, enabled the acidity of 1 to be determined (∆H°a cid ) 402 ( 2 kcal/mol). Good agreement is found with the 298 K computed MP2/6-31+G(d)//HF/6-31+G(d) value of 405.1 kcal/mol. In a similar manner, the electron affinity of dodecahedryl radical was measured (EA ) 4 ( 2 kcal/mol). These results were combined in a thermodynamic cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Multifunctional ligands with approximately tetrahedral angles between the ligand moieties can be derived from di-, tri-, and tetraphenylmethane. However, the Si analogues (i.e., di-, tri-, and tetraphenylsilanes; see Figure ) are generally easier to synthesize, because of the availability of coupling reactions between aryllithium compounds and chlorosilanes. Thus, tetraphenylsilane is considerably easier to prepare than tetraphenylmethane. Still, even among the oligoarylsilanes, some derivatives have presented synthetic challenges: for example, Wuest et al reported that tetrakis(4-formylphenyl)silane was difficult to prepare in pure form .…”
Section: Resultsmentioning
confidence: 99%
“…Multifunctional ligands with approximately tetrahedral angles between the ligand moieties can be derived from di-, tri-, and tetraphenylmethane. However, the Si analogues (i.e., di-, tri-, and tetraphenylsilanes; see Figure ) are generally easier to synthesize, because of the availability of coupling reactions between aryllithium compounds and chlorosilanes. Thus, tetraphenylsilane is considerably easier to prepare than tetraphenylmethane. Still, even among the oligoarylsilanes, some derivatives have presented synthetic challenges: for example, Wuest et al reported that tetrakis(4-formylphenyl)silane was difficult to prepare in pure form .…”
Section: Resultsmentioning
confidence: 99%
“…Calculated energy differences between the axial (1a) and equatorial (1b) geometries are typically 3-4 kcal/mol. Kass and coworkers have previously shown that bulky substituents tend to occupy the axial position in pentavalent siliconates [75], and it has also been suggested that the substituents may prefer the axial position because they are more electronegative than the methyl groups [76].…”
Section: Computational Resultsmentioning
confidence: 99%
“…What are the ring strain energies of the simple hydrocarbon rings, cyclopropane (28) and cyclobutane (29)? These rings are made up of methylene groups, CH 2 fragments, just like the interior carbons in straight-chain, unstrained alkanes.…”
Section: Ring Strain Energymentioning
confidence: 99%
“…For this discussion, we will determine the RSE of cyclobutane (29), cyclobutene (30), and oxetane (31). Three methods for generating an appropriate chemical reaction have found utility: the isodesmic reaction, the homodesmotic reaction, and the group equivalent reaction.…”
Section: Ring Strain Energymentioning
confidence: 99%